Teachers' Community Involvement in Fee-Free Basic Education in Tanzania: A systematic Literature Review - Issa Yusuph; Michaela Mhagama; Prospery Mwansa Mwila (PT. Pusmedia Group Indonesia, 2026)
Teachers' community involvement has increasingly been recognized as a critical factor in the successful implementation of Fee-Free Basic Education (FFBE), particularly in developing countries where educational reforms require strong collaboration among schools, families, and local communities. This study systematically reviewed empirical evidence on the contribution of teachers' community involvement to the implementation of Fee-Free Basic Education and examined the challenges constraining effective community engagement. The review was guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant studies were identified through systematic searches of peer-reviewed journal articles, books, policy reports, and scholarly publications obtained from major academic databases, including Scopus, Web of Science, ERIC, Google Scholar, and institutional repositories. Studies published in English that addressed teachers' community engagement and education policy implementation were included, while duplicate records, opinion papers, conference abstracts, and studies lacking empirical evidence were excluded. The selected studies were screened, assessed for eligibility, and synthesized thematically. The review indicates that teachers' community involvement substantially enhances the implementation of Fee-Free Basic Education by strengthening stakeholder collaboration, improving communication between schools and communities, promoting shared decision-making, increasing accountability, mobilizing local resources, and improving learner attendance and participation. Evidence further suggests that schools characterized by strong teacher-community partnerships are more capable of sustaining educational reforms and responding to contextual challenges than those operating with limited stakeholder engagement. However, the review also identifies persistent barriers, including inadequate institutional support, increasing teacher workloads, socio-economic constraints, limited parental awareness, weak participatory leadership, and insufficient professional preparation for community engagement. The review concludes that community involvement should be institutionalized as an integral component of Fee-Free Basic Education implementation rather than treated as a complementary activity. Strengthening teachers' competencies in community engagement, promoting participatory school leadership, and establishing supportive policy frameworks are essential for enhancing educational quality and ensuring the long-term sustainability of education reforms, particularly within resource-constrained contexts.